The Influence of Service Quality, Customer Value and Customer Expectations on Customer Satisfaction of Commuter Line Train Services - Ratnawita Ratnawita; Bord Nandre Aprila; Abdurohim; Eki Candra; Tengku Kespandiar (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
The purpose of this study is to ascertain how customer happiness among users of commuter trains is influenced by customer expectations, customer value, and service quality. Multiple linear regression has been employed as the analytical technique. The distribution of questionnaires is the primary method of data gathering in this quantitative study. Accidental sampling is the method employed. Participants in this study were commuter service users from Jabodetabek. Between September and October of 2022, this study was carried out at a number of commuter train starting points, transit stations, and terminating points. Accidental sampling was the method used in this investigation. Questionnaires are distributed to gather this data. The customer expectation variable has no impact on customer satisfaction for consumers of the Jabodetabek commuter rail service, according to the research findings. Customers of the Jabodetabek commuter train service are significantly more satisfied when the customer value variable is taken into account. Customers who utilize the Jabodetabek commuter train service are significantly more satisfied when the service quality variable is taken into account. Consumer happiness is significantly influenced simultaneously by customer expectations, customer value, and service quality.